Review: Maximi Confessoris Liber Asceticus - Louth, Andrew (The journal of theological studies, 2003)
Maximi Confessoris Liber Asceticus Peter van Deun Steven Gysens cclxviii + 259 Turnhout (Corpus Christianorum Series Graeca, 40.) Brepols Leuven Leuven University Press 2000 Hardback€234 2 503 40401 4 Paperback€221 2 503 40402 2